2013
DOI: 10.1302/0301-620x.95b11.32900
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular protrusio

Abstract: There are few reports describing the technique of managing acetabular protrusio in primary total hip replacement. Most are small series with different methods of addressing the challenges of significant medial and proximal migration of the joint centre, deficient medial bone and reduced peripheral bony support to the acetabular component. We describe our technique and the clinical and radiological outcome of using impacted morsellised autograft with a porous-coated cementless cup in 30 primary THRs with mild (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
2
0
4
Order By: Relevance
“…This echoes findings from previous studies, which have shown satisfactory outcomes in this patient population. 11 12 13 14 15 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This echoes findings from previous studies, which have shown satisfactory outcomes in this patient population. 11 12 13 14 15 16 …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has demonstrated satisfactory short- and long-term outcomes for patients with AP who undergo THA. 11 12 13 14 15 16 However, a higher level of anatomical complexity associated with these cases exists, including insufficient acetabular bone stock and loss of standard surgical landmarks. This can lead to improper acetabular component placement and potentially increased rates of aseptic loosening, instability, and the need for revision surgery.…”
mentioning
confidence: 99%
“…La literatura describe varias técnicas para alcanzar un adecuado press-fit cuando se emplean copas no cementadas, desde un underreaming de 2 mm, hasta un reaming de 1 mm de línea a línea. [28][29][30] En nuestra experiencia utilizamos 1 mm de underreaming con una copa completamente hemisférica y no elíptica técnica validada en la literatura para el implante que utilizamos. [30][31][32] En nuestro caso, el componente de prueba es considerado imprescindible para estos pacientes, para asegurarse que la cantidad de injerto a utilizar en el fondo es adecuada.…”
Section: Preparación Del Acetábulounclassified
“…[28][29][30] En nuestra experiencia utilizamos 1 mm de underreaming con una copa completamente hemisférica y no elíptica técnica validada en la literatura para el implante que utilizamos. [30][31][32] En nuestro caso, el componente de prueba es considerado imprescindible para estos pacientes, para asegurarse que la cantidad de injerto a utilizar en el fondo es adecuada. La abducción y la anteversión de la copa las verificamos con la técnica de Meftah-Ranawat.…”
Section: Preparación Del Acetábulounclassified
See 1 more Smart Citation